Science Stories, life stories: Engaging the sciences through feminist science fiction - Merrick, Helen (Elsevier Ltd, 2010)
Despite the groundbreaking work of feminist science scholars, the "two culture" divide between the science and humanities remains pronounced in feminist scholarship. As critics such as Elizabeth Wilson and Vicki Kirby have observed, much feminist philosophy fails to engage with scientific understandings of "life" in their accounts of gendered subjectivity and embodiment. One area where feminist work in both the sciences and the arts may be seen to productively converge is in feminist science fiction (SF). This article argues that feminist SF could be a vital participant in 'cross-cultural' feminist conversations about the cultures and discourses of the natural sciences, through a close reading of the 2004 novel Life, by Gwyneth Jones.